Trends and Outcomes of Aortic Valve Replacement in Patients With Diabetes in the US - Khan, Sarah; Dargham, Soha; Al Suwaidi, Jassim; Jneid, Hani; Abi Khalil, Charbel (Frontiers in Cardiovascular Medicine, 2022)
Aims: We aimed to assess the trend and outcome of aortic valve replacement in patients with diabetes. Background: Diabetes is associated with higher cardiovascular events. Methods: Data from the National Inpatient Sample was analyzed between 2012 to 2017. We compared hospitalizations and in-hospital cardiovascular outcomes in patients with diabetes to those without diabetes, hospitalized for aortic valve replacement. Results: In diabetes patients undergoing TAVR, the mean age of participants decreased from 79.6 ±8 to 67.8 ±8, hospitalizations increased from 0.97 to 7.68 /100 000 US adults (p<0.002 for both). There was a significant temporal decrease in mortality, acute renal failure (ARF), and stroke. Compared to non-diabetic patients, those with diabetes had a higher risk of stroke, ARF, and pacemaker requirement (adjusted OR= 1.174 [1.03-1.34], 1.294 [1.24-1.35], 1.153 [1.11-1.20]; respectively), but a similar adjusted mortality risk. In diabetes patients undergoing sAVR, the mean age of participants decreased from 70.4 ±10 to 68 ±9 (p<0.001), hospitalizations dropped from 7.72 to 6.63 / 100 000 US adults (p=0.025), so did mortality, bleeding, and ARF. When compared to non-diabetes patients, those with diabetes were older and had a higher adjusted risk of mortality, stroke, and ARF (adjusted OR= 1.115 [1.06-1.17], 1.140 [1.05-1.23], 1.217 [1.18-1.26]; respectively). Conclusion: The recent temporal trend of aortic valve replacement in patients with diabetes shows a significant increase in TAVR coupled with a decrease in sAVR. Mortality and other cardiovascular outcomes decreased in both techniques. sAVR, but not TAVR, was associated with higher in-hospital mortality risk.